Justified in the Spirit : creation, redemption, and the triune God - Macchia, Frank D., 1952- (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2010)
"The Pentecostal Manifestos series aims to speak for and to a rising, outward-looking generation of Pentecostal scholarship. Written by both established and newly emerging scholars, the various "manifesto" volumes will be creative statements, marked by rigorous theological scholarship, reflecting a distinctly Pentecostal engagement with wider themes and concerns in Christian thought today." "The Second Volume of the groundbreaking Pentecostal Manifestos series, Frank Macchia's Justified in the Spirit offers a pneumatological, Pentecostal-friendly theology of justification by faith that is broadly Trinitarian, ecclesiological, and eschatological in orientation." ""It is a necessary and new perspective to see the justification of the sinner embraced by the life-giving Spirit. Frank Macchia's book is a great step forward toward a full Trinitarian concept of salvation.... A rich book full of solutions to old theological problems."Jnrgen Moltmann, University of Tilbingen" ""Argues persuasively that Christian teaching about the Spirit (pneumatology) has much to offer to a correct understanding of justification.... We have here a book of singular consequence."William G. Rusch, Yale Divinity School" ""A noted systematician and ecumenist, Macchia gleans from his own Pentecostal tradition in his intriguing revisioning and reorientation of the major soteriological concept of justification by faith."Veli-Matti KSrkkSinen, Fuller Theological Seminary University of Helsinki" ""With Macchia's Justified in the Spirit Pentecostal systematic theology has come of age.... Catholics and Protestants will no longer be able to attribute a secondary role to the Spirit, while Pentecostals will discover the hidden treasures that their movement signifies."Ralph Del Colle, Marquette University"--BOOK JACKET.
Introduction : framing the issue of justification and the spirit -- Imparted righteousness : the catholic view of justification -- Imputed righteousness : the protestant view of justification -- Justification and spirit baptism : the exploration of a pentecostal metaphor -- The promise of the spirit : justifying righteousness in the old testament -- Apart from us : justification and the spirit-indwelt christ -- Embracing us : justification and spirit baptism -- Participation : by the spirit through faith -- The spirit and the other : the justified community -- The embrace of the spirit : toward a trinitarian theology of justification -- Justified in the spirit : a concluding reflection.
Includes bibliographical references (p. 319-333) and indexes.
Keywords: Justification (Christian theology); Pentecostal churches -- Doctrines